2014
DOI: 10.3109/10826084.2013.776084
|View full text |Cite
|
Sign up to set email alerts
|

From “Kickeando las malias” (Kicking the Withdrawals) to “Staying clean”: The Impact of Cultural Values on Cessation of Injection Drug Use in Aging Mexican-American Men

Abstract: Drug use among older adults is a growing concern, particularly for the burgeoning Hispanic population. Older adults seeking drug treatment will double over the next decade to almost 6 million. Cultural factors influence drug use, and more specifically, Hispanic cultural values influence heroin use. This study explored Mexican-American injection drug users' adherence to traditional Hispanic cultural values and their impact on cessation. Ethnographic interviews endorsed contextualized influences of values on her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
(109 reference statements)
1
9
0
Order By: Relevance
“…On the contrary, our findings suggest that familismo may actually pose as a risk factor for addiction. This finding is supported by other research showing that the family environment is a risk factor for heroin relapse [10, 18] and continuation of substance use [31]. Our finding on the paradoxical role of family in both encouraging and discouraging participants’ drug use further reflects the mixed nature of the current literature.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the contrary, our findings suggest that familismo may actually pose as a risk factor for addiction. This finding is supported by other research showing that the family environment is a risk factor for heroin relapse [10, 18] and continuation of substance use [31]. Our finding on the paradoxical role of family in both encouraging and discouraging participants’ drug use further reflects the mixed nature of the current literature.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the drug use behaviors of Hispanic individuals may be in response to cultural scripts that support or oppose these behaviors. Cultural values have been shown influence both the initiation and cessation of drug use in this population [10]. …”
Section: Introductionmentioning
confidence: 99%
“…The inability of Russian men to demonstrate subsequent masculinity has been found to be associated with worry, depression, and sleep disorders (Rimashevskaia, 2008). Similar phenomena were reported by Flores et al (2014), who found that cultural values emphasizing masculinity prevented Hispanic drug users from seeking treatment.…”
Section: Russian Speaking Patients In Rehabilitation Centersmentioning
confidence: 68%
“…Paradoxically, the same cultural features that lead to heavy drug abuse and impede involvement in treatment, can contribute to higher rates of successful rehabilitation by Russian-speaking patients. This complex relationship between culture and drug addiction was previously mentioned by Flores et al (2014) who suggested that cultural values may both inhibit as well as enable recovery.…”
Section: Russian Speaking Patients In Rehabilitation Centersmentioning
confidence: 78%
See 1 more Smart Citation